GE_GERICHTE P/13293/2018 vom 19. August 2020 - GE Cour de justice (2020)
MEURTRE;TENTATIVE(DROIT PÉNAL);FIXATION DE LA PEINE;DÉTENTION PROVISOIRE;IMPUTATION;EXPULSION(DROIT DES ÉTRANGERS);TORT MORAL;DÉFENSE D'OFFICE | CP.111; CP.22.al1; CP.47; CP.51; CP.66A.al1.letA; CO.47; CPP.135.al1